Formation of hollow MoO2@C nano‐octahedrons using polyoxometalate‐based metal‐organic framework as a template for enhanced lithium‐ion batteries. (15th February 2021) - Wang, Yu; Zhao, Hongsheng; Di, Andi; Yang, Xu; Cong, Bowen; Chen, Gang
Summary: Unique hollow MoO2 @C nanoparticles are synthesized in situ by the polyoxometalate‐based metal‐organic framework as a precursor. Characteristic results show that the prepared MoO2 @C nanoparticles have a narrow size distribution, and the C, mainly constituted by graphitic carbon, connects with the MoO2 . Such a special structure guarantees a high electrical conductivity and high chemical stability of the synthesized MoO2 @C composite material. MoO2@C composite material can provide a high reversible capacity of 1134 mAh g −1 at a current density of 500 mA g −1 after 200 cycles, and has a capacity retention of 88.24%. What's more, while the current density is doubled, the capacity stabilizes at 720 mAh g −1, of which 81% is retained after 800 cycles. This work highlights that nanostructure design makes contributions to achieving advanced energy storage materials and provides a new concept of preparing organic‐inorganic hybrid materials for energy storage. Abstract : Hollow MoO2 @C nanoparticles are synthesized in situ using a polyoxometalate‐based metal‐organic framework as a precursor. This work highlights that nanostructure design is an effective strategy to achieve advance energy storage materials and provides a new concept of preparing organic‐inorganic hybrid materials for energy storage.